Transactional analysis in health care - "Elder, Jean" (London, 1978)
Transactional Analysis (TA) is a fresh and effective approach to inter-personal relating and communicating. Students enjoy learning and applying it to themselves, each other, teachers, hospital staff, and, most importantly, to patients. In this book, basic TA theory is applied to health care and illustrated with examples from the experience of nursing students. Although it is primarily intended for students in collegiate nursing pro-grams, it is relevant for in-service and continuing education as well.
Keywords: Transactional analysis